Pendekatan Sistem dan Pemecahan Masalah Pendidikan - Amiruddin, Amiruddin; Yunita, Era; Sari, Maulina; Siregar, Siti Masdelina; Lailan, Tengku (MODELING: Jurnal Program Studi PGMI, 2023)
Developing effective school management needs to pay attention are two basic components namely inputs and processes. Component inputs need to be considered to comply with minimum service standards (SPM) or the national standard (NS) at each school level (elementary, junior high school and vocational school). SPM/SN at every level of the school include: currulum, teacher/staff, students, facilities, financial, organizational, and environmental support (government, society, and parents). Although SPM was the main concern, does not mean that good schools are exclusive, in which only certain groups of students (intelligent or able to be economically) are accepted. Nor does it mean that schools should have a versatile facility and infrastructure to realize the luxury of a good school.